Herding livelihoods in transition: Kenya's Kitengela Olmakao Cultural Village - International Livestock Research Institute (International Livestock Research Institute, 2012)
This is the story of a group of women from the Kitengela rangelands area, which boarders the Kenyan capital of Nairobi, who have come together to form the Olmakao Cultural Village to provide alternative sources of income to their livestock-based livelihoods in the face of increasingly frequent droughts that have decimated their herds.